The determinants of Malaysian Real Estate Investment Trusts (M-REIT’S) price movement / Aniq Shardin and Intan Nurazimah Abdul Malik - Shardin, Aniq; Abdul Malik, Intan Nurazimah (Faculty of Business and Management, 2013)
This paper focuses on how market risk, economic activities, inflation rate, interest rate, and foreign direct investment inflow in term of GDP percentage affects M-REIT’s price movement using M-REIT’s average price data from 1997 to 2012. Data such as average MREIT price, interest rate, inflation rate and foreign direct investment are obtained from World Bank and Bursa Malaysia website. The findings suggest that significant relationship affects average M-REIT’s price movement. Furthermore, based on the result a negative relationship between REIT with inflation rate, interest rate and foreign direct investment depending on the economic situation is documented. However, there is significant link between REIT with inflation rate, interest rate except foreign direct investment. In term of significant relationship between interest rate and inflation towards REIT is self-managed, or type of property investment in which the REIT specializes. However, a negative correlation exists between the independent variables which are interest rate, inflation rate and foreign direct investment in relation to M-REIT average price movement suggesting that decreased in those macroeconomics variables will reduced M-REIT’s price.